Bioengineered Skin - Escámez, María José; Martínez-Santamaría, Lucía; García, Marta; Guerrero-Aspizua, Sara; Carretero, Marta; Larcher, Fernando; Meana, Álvaro; Río, Marcela Del (IntechOpen, 2011)
None